A study on internet usage among the new and final year students in Universiti Teknologi MARA, Shah Alam / Cheryl Frederick Asu and Norhaslinda Mohd Ramli - Asu, Cheryl Frederick; Mohd Ramli, Norhaslinda (2005)
There is much excitement about the use of internet. This is due to the fact that internet had become a vital part in our daily life. Ineternet had become more than a communication tool but also as a source of gathering and retrieving information.